Association between Previous Statin Use and Alzheimer’s Disease: A Nested Case-Control Study Using a National Health Screening Cohort - Ji Hee Kim; Heui Seung Lee; Jee Hye Wee; Yoo Hwan Kim; Chan Yang Min; Dae Myoung Yoo; Hyo Geun Choi (Brain Sciences, 2021)
A number of studies report the incidence of Alzheimer’s disease (AD) in patients taking statins, but the results are inconsistent. (1) Background: The present study investigated the cross-sectional association between previous statin use and the risk of AD development in Korean residents. (2) Methods: We used the Korean National Health Insurance Service-National Sample Cohort; 17,172 AD patients were matched by age, gender, income, and region of residence with 68,688 control participants at a ratio of 1:4. We used a multiple conditional logistic regression model to analyse the association between the number of days of statin use and AD occurrence. Further analyses were performed to identify whether this association is maintained for different ages, genders, socioeconomic status groups, and covariates. (3) Results: The odds ratio, which was adjusted for potential confounders, for the days of statin use per year in the AD group compared to the control group was 0.95 (95% confidence interval = 0.92–0.98; p = 0.003). The number of days of statin use in the AD group was significantly smaller in the subgroups of non-smokers and individuals with normal weight, alcohol consumption less than once a week, total cholesterol level below 200 mg/dL, systolic blood pressure below 140, diastolic blood pressure below 90, and fasting blood glucose below 100 mg/dL. (4) Conclusions: Our results suggest that statin use prevents the occurrence of AD. The effects of statin use in preventing AD may be greater in individuals at relatively low risk.